(untitled) (American Journal of Islam and Society, 2020)
In an editorial essay, Ovamir Anjum reflects on the current moment of (and literature on) de-globalization, considering in turn conservative and liberal arguments. He concludes by raising several questions which de-globalization opens, key among them the challenges posed by ongoing ecological degradation. In the first research article, Timothy Gutmann offers the term “propaedeutic” to refer to the critical pedagogy necessary for teaching unfamiliar material to audiences whose sensibilities and expectations are already structured by distinctive anxieties and concerns. Gutmann addresses common caricatures of Islamic law and suggests that Islamic traditions may themselves contain a propaedeutic potential for teaching Islamic studies in the North American context. In the second research article, Brannon Wheeler traces a possible Islamic “Responsibility To Protect.” By focusing on Islamist exegesis of Q 3:110 and on classical and contemporary understandings of migration, Wheeler ultimately notes the political and intellectual compromises involved in accepting certain instances of violence and rejecting others. In the third research article, Abbas Ahsan makes an analytic-philosophical case for radical epistemic relativism. Our inability to conceive of the logically impossible, he concludes, is itself a testimony that God transcends the laws of logic. Next, a review essay is followed by ten book reviews; in this issue’s Forum article, Scott Lucas introduces readers to the sophisticated work of four Muslim thinkers of the 5th/11th century: Miskawayh, al-Hakim al-Jishumi, Ibn Hazm, and al-Khatib al-Baghdadi. Lucas encourages Muslims to emulate these figures’ practices of reading widely, with intellectual generosity and commitment, and to insist on the relationship between knowledge and practice. Introductory Note by Dr. Shuruq Naguib Editorial by Dr. Ovamir Anjum